APLIKASI PUPUK ORGANIK DENGAN ANORGANIK TERHADAP TANAMAN SAWI (Brassica juncea, L.) - Panri M. Pardede; Armaini '; Sukemi Indra Saputra (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The research aimed to improve the growth, production of sawi and get better dose. The research carried out in the Technical Services Unit Faculty of Agriculture University of Riau from January to February 2014 and conducted experiments used Randomized Block Design (RBD) is P0, P1, P2, P3 and P4 (without organic fertilizer, green manure Calopogonium muccunoides 20 ton / ha (3 kg / plot), chicken manure 20 ton / ha (3 kg / plot), green manure Calopogonium muccunoides 10 ton / ha + ½ urea recommended and chicken manure 10 ton / ha + ½ urea recommended). The parameters measured were plant height, leaf area, leaf number, fresh weight and fresh weight for consumption. The data were analyzed used analysis of variance and continued DNMRT at 5% level. The result showed that 1,5 kg chicken manure + ½ urea recommended and green manure Calopogonium muccunoides 1,5 kg + ½ urea recommended better dose for the growth and production of sawi. Keywords: urea fertilizer, organic fertilizer, sawi